1997
DOI: 10.1177/027112149701700308
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the State Department of Education in Promoting Integrated Placement Options for Preschoolers

Abstract: This article summarizes a qualitative research study sponsored by the Virginia Department of Education. Recommendations to the department to promote more opportunities for preschool integration were elicited from focus group and individual interviews with representatives from 11 Virginia school divisions that were providing integrated preschool programs. Recommendations included the provision of written information, staff development, changes in current personnel preparation, financial support, and state-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the present study, a majority of preschool teachers indicated that an early childhood special education teacher (71%), an early childhood or preschool teacher (59%), or a teaching assistant who was jointly supervised by preschool classroom and special education teachers (59%) could appropriately provide specialized one-to-one intervention recommended for a preschool child with disabilities, in addition to intervention which occurred in preschool activities or at home, if they received appropriate training or support. The importance of the availability of training and support is frequently mentioned as a key to successful inclusive programs (Bennett, Deluca, & Bruns, 1997;DEC, 1993;Harvey, Voorhees, & Landon, 1997;McDonnell et al, 1997;Wolery, Werts, Caldwell, & Snyder, 1995). Unfortunately, recent surveys indicate that such support is all too frequently unavailable in preschool programs (Gemmell-Crosby & Hanzlik, 1994;McDonnell et al, 1997;.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a majority of preschool teachers indicated that an early childhood special education teacher (71%), an early childhood or preschool teacher (59%), or a teaching assistant who was jointly supervised by preschool classroom and special education teachers (59%) could appropriately provide specialized one-to-one intervention recommended for a preschool child with disabilities, in addition to intervention which occurred in preschool activities or at home, if they received appropriate training or support. The importance of the availability of training and support is frequently mentioned as a key to successful inclusive programs (Bennett, Deluca, & Bruns, 1997;DEC, 1993;Harvey, Voorhees, & Landon, 1997;McDonnell et al, 1997;Wolery, Werts, Caldwell, & Snyder, 1995). Unfortunately, recent surveys indicate that such support is all too frequently unavailable in preschool programs (Gemmell-Crosby & Hanzlik, 1994;McDonnell et al, 1997;.…”
Section: Discussionmentioning
confidence: 99%
“…Among their concerns were adequate provision for traine ing and willingness of key staff members and community advocates (especially parents) to adopt the innovation and integration of program philosophies from the early childhood and special education programs. Harvey, Voorhees, and Landon (1997) also studied factors that contributed to the development of inclusive preschool programs in Virginia. Using focus groups of key stakeholders-early childhood education administrators and teachers, early childhood special education administrators and teachers, parents of preschoolers with disabilities, and university faculty members who were collaborating with these programs, they asked the groups to identify concerns and issues surrounding the creation of inclusive programs.…”
mentioning
confidence: 99%